Workshop Staff Detection Method Based on Spatial Domain Attention Mechanism - LI Cheng-yan; MA Jin-tao; ZHAO Shuai (Journal of Harbin University of Science and Technology, 2022)
Workshop staff detection is to use the target detection technology to detect the staff in the corresponding area of the factory production workshop, to ensue the life, health and safety of the staff in the production workshop. In this paper, the improved dark channel priority processing strategy is applied to image enhancement and SSD (single shot multibox detector) which combines spatial attention mechanism detector (detector) network improves the detection efficiency while ensuring the real-time requirements. It is verified on the test set and VOC data set in this paper, and the results show that the positioning effect and detection rate are better.